PENETAPAN KADAR STEROID PADA EKSTRAK DAUN TITANUS (Leea aequata L.) SECARA SPEKTROFOTOMETRI UV-VIS - Dian Ika Perbina; Jhan Saberlan Purba (Jurnal Penelitian Farmasi & Herbal, 2021)
The titanus plant (Leea aequata L.) is a plant that used as traditional medicine. The stems and roots are used as astringent, anthelmintic, indigestion, jaundice, chronic fever and malaria. The leaves and twigs are used as an antiseptic and to treat wounds. Steroids are secondary metabolites that have a compound structure that quite diverse. Steroids have a pharmacological effect on lowering cholesterol and anticarcinogenic. The objective of the research to determine the steroid levels in titanus leaf extract (Leea aequata L.). The analytical method used is qualitative with reagents Lieberman-Bouchard and quantitative uv-vis spectrophotometry with wavelength of 423 nm. The results of the qualitative analysis of the positive samples contained steroid compounds. The Results quantitative content of ethanol extract of titanus leaf 30.8889 mg/g, and quantitative results ethyl acetate extract content of titanus leaves 72.2649 mg/g. Validity test results obtained linearity test r=0.9994, RSD of ethanol extract 0,2852% and ethyl acetate extract 8,1120%, recovery of 101% ethanol extract and 103.667% ethyl acetate extract, LOD 2.2078 and LOQ 7,3593. SPSS analysis results p=0.000 (p<0.05). Based on the results of the research that has been done, it can be concluded that uv-vis spectrophotometry can be used to determine total steroid content of titanus leaf extract (Leea aequata L.).